Energy consumption and foreign direct investment: a panel data analysis for Portugal - Leitão, Nuno Carlos (2015)
This research considers the relationship between energy consumption and foreign direct investment (FDI) for the period 1990-2011. As econometric strategy, we use unit root test and panel data. The empirical results illustrate that the income per capita and political globalization present a positive impact on energy consumption. The selected components of globalization (cultural, social and political) show that these variables promote Portuguese foreign direct investment. The econometric models also considered two control variables, trade openness and exchange rate. These proxies are positively correlated with FDI. The variables of income per capita and the squared income per capita validate the environmental Kuznets curve assumptions.